Consumer perception and preference for suboptimal food under the emerging practice of expiration date based pricing in supermarkets. (January 2018) - Aschemann-Witzel, Jessica
Highlights: Likelihood of choice of suboptimal food to curb food waste in retail is explored. Communication about price reduced food close to expiration date is tested. Communication of food waste avoidance differently affects men and women. Perceived quality and likelihood of consuming food entirely impact likely choice. Choice of suboptimal food can be furthered through increasing familiarity and providing information. Abstract: Consumers have been found to majorly prefer 'optimal' food over 'suboptimal' when purchasing food. To provide an incentive for consumers to select suboptimal food and thus decrease food waste in the supply chain, expiration date based pricing is suggested and increasingly applied. However, it is unclear which contextual, individual, and product-related factors impact consumer likelihood of choice and thus acceptance of the practice in the long run. The study aimed at exploring the effect of communicating different motives for purchase, the product being organic, familiarity with the practice, individual preferences, and product-related factors. An online survey experiment among 842 Danish consumers realistically mimicked the current market context. Findings reveal that neither communicating budget saving or food waste avoidance nor the product being organic has an influence. However, there is a gender effect when the practice is communicated as a food waste avoidance action. Consumer's familiarity with the practice has a significant influence, as has the individual giving importance to the price criterion, age, and education. Food category differences are explored, showing that familiarity and the interaction with gender is observed for milk in particular. Overall, perceived quality and estimated likelihood of consumption at home majorly determine likelihood of choice. Consumer acceptance of expiration date based pricing of suboptimal food can be increased through furthering consumer familiarity with the practice, improving perceived quality and providing tips to ensure consumers are confident to be able to use the entire food at home.